Origin of the Mobile Di-Hydro-Pteroate Synthase Gene Determining Sulfonamide Resistance in Clinical Isolates - Sánchez-Osuna, Miquel; Cortés, Pilar; Barbé, Jordi; Erill, Ivan (Frontiers in Microbiology, 2019)
Sulfonamides are synthetic chemotherapeutic agents that work as competitive inhibitors of the di-hydro-pteroate synthase (DHPS) enzyme, encoded by the folP gene. Resistance to sulfonamides is widespread in the clinical setting and predominantly mediated by plasmid- and integron-borne sul1-3 genes encoding mutant DHPS enzymes that do not bind sulfonamides. In spite of their clinical importance, the genetic origin of sul1-3 genes remains unknown. Here we analyze sul genes and their genetic neighborhoods to uncover sul signature elements that enable the elucidation of their genetic origin. We identify a protein sequence Sul motif associated with sul-encoded proteins, as well as consistent association of a phosphoglucosamine mutase gene (glmM) with the sul2 gene. We identify chromosomal folP genes bearing these genetic markers in two bacterial families: the Rhodobiaceae and the Leptospiraceae. Bayesian phylogenetic inference of FolP/Sul and GlmM protein sequences clearly establishes that sul1-2 and sul3 genes originated as a mobilization of folP genes present in, respectively, the Rhodobiaceae and the Leptospiraceae, and indicate that the Rhodobiaceae folP gene was transferred from the Leptospiraceae. Analysis of %GC content in folP/sul gene sequences supports the phylogenetic inference results and indicates that the emergence of the Sul motif in chromosomally-encoded FolP proteins is ancient and considerably predates the clinical introduction of sulfonamides. In vitro assays reveal that both the Rhodobiaceae and the Leptospiraceae, but not other related chromosomally-encoded FolP proteins confer resistance in a sulfonamide-sensitive Escherichia coli background, indicating that the Sul motif is associated with sulfonamide resistance. Given the absence of any known natural sulfonamides targeting DHPS, these results provide a novel perspective on the emergence of resistance to synthetic chemotherapeutic agents, whereby preexisting resistant variants in the vast bacterial pangenome may be rapidly selected for and mobilized upon the clinical introduction of novel chemotherapeuticals.